The effect of physical disability of home based stroke persons on their quality of life in Kelantan - Maswan, Noor Azira (Universiti Sains Malaysia, 2009)
The goal of this study is to determine the effect of physical disability of stroke patients on their quality of life in Kelantan. This study examines the effect of demographic characteristics and patients' physical disability on quality of life among stroke patients. Forty five stroke patients participated in the study. Data were selected trough purposive sampling. Subjects were asked to respond to one set of questionnaires which is consisted of 3 parts: 1) demographic characteristics, 2) Barthel Index and 3) EQ5D with scale. A pilot study had been done and the reliability was 0.93 and 0.62, respectively. Subjects who had involve in this study: 53.3% were female, 91 .1% were Malay and Muslim, age ranged from 31 to 90 years (M = 62.18, SO = 13.38), with all were married. Majority of the subjects' education level was secondary school and only 11.1% attained Diploma/College/University. For the employment status, 75.6% were unemployed with the highest total income household monthly was in range RM 500 to RM1000. Majority of the subjects having ischemic stroke (73.3%) and the stroke life span more than 3 month to 6 month. There are also different means for each demographic characteristic. While the physical disability and quality of life had correlation with p=0.05. Physical disability among stroke persons will alter their quality of life. As a health professional, the information in this study may help in understanding stroke patient needs and the best treatment for them.